Multiple neuronal populations control the eating behavior in Hydra and are responsive to microbial signals - Giez, Christoph; Pinkle, Denis; Giencke, Yan; Wittlieb, Jörg; Herbst, Eva-Maria; Spratte, Tobias; Lachnit, Tim; Klimovich, Alexander; Selhuber-Unkel, Christine; Bosch, Thomas C. G. (Current biology, 2023)
Although recent studies indicate the impact of microbes on the central nervous systems and behavior, it remains unclear how the relationship between the functionality of the nervous system, behavior, and the microbiota evolved. In this work, we analyzed the eating behavior of Hydra, a host that has a simple nervous system and a low-complexity microbiota. To identify the neuronal subpopulations involved, we used a subpopulation-specific cell ablation system and calcium imaging. The role of the microbiota was uncovered by manipulating the diversity of the natural microbiota. We show that different neuronal subpopulations are functioning together to control eating behavior. Animals with a drastically reduced microbiome had severe difficulties in mouth opening due to a significantly increased level of glutamate. This could be reversed by adding a full complement of the microbiota. In summary, we provide a mechanistic explanation of how Hydra’s nervous system controls eating behavior and what role microbes play in this.